Winter adaptive sports participation, injuries, and equipment - Oh, H.; Johnson, W.; Syrop, I. P. (Sports Medicine and Arthroscopy Review, 2019)
As the participation rate and popularity of winter adaptive sports increases, understanding injury patterns and equipment is crucial for athletes, coaches, athletic trainers, sports physicians, prosthetists/orthotists, and all the staff involved. While the inaugural Winter Paralympics in 1976 had 17 participating countries, the most recent paralympic games in Pyeongchang, South Korea had >500 athletes from 49 different countries competing in 6 disciplines: alpine skiing, nordic skiing, sledge hockey, wheelchair curling, biathlon, and snowboarding. In this paper, we review participation rates, injury trends and equipment, with a focus on the 3 most popular events: alpine skiing, nordic skiing, and sledge hockey. Despite injury risk within this athletic community, there are documented advantages to physical movement, and for each individual the risks of injury have to be weighted with the benefits of competing. Overall, there is a need for educational efforts regarding the development, access, and participation to injury prevention programs with an integrated and multidisciplinary approach.